Foreign Investment Promotion Analysis in Sultanate of Oman: The Case of Dhofar Governorate - Pauceanu, Alexandrina Maria (International Journal of Economics and Financial Issues, 2016)
The stiff rate of competition among the developing countries to attract foreign investments in the regions of their countries has created the deeper understanding of the main foreign direct investment (FDI) incentive. It is obvious that the foreign investment became a priority for most of the governments. This research paper aimed at examining the main approaches and factors in foreign investment promotion within Dhofar Governorate in Sultanate of Oman. Data collected from relevant scholarly papers and government reports, interviews with officials in charge of foreign investment promotion and the conclusions from participation in meetings and public debates have been utilized in the analysis. Economic and political stability are among the factors which actually motive foreigners to invest in the region. Additionally, high purchasing power, a big market size and low cost of doing business in the region has been reported to be very desirable. It is evidence that the government from Sultanate of Oman have promoted aspects of foreign investments by offering a number of incentives such as favorable government policies and laws, and offering lower tax rates, creating free zones, business incubators, etc. Keywords: foreign direct investments, Oman, investment incentives, GCC, foreign promotion efficiency, Dhofar, free zone JEL Classifications: O53, P45